Lizard as spreader of Salmonella Bacteria: significant and interaction methods according to fiqh al-Hadith / Mohd Farhan Md Ariffin ... [et al.] - Md Ariffin, Mohd Farhan; Ahmad, Khadher; Ramli, Mohd Anuar; Abu Bakar, Ahmad Bakrin Sofawi (Universiti Teknologi MARA, Perlis, 2016)
In early year 2016, Malaysia uproar when international media reported that there was an infection of salmonella on salad and tomato products imported from Australia and altogether raise anxiety among society. Salmonella is a bacterium which causes infectious disease called salmonellosis and inhabit humans and animal intestines. Among the causes of salmonella bacteria outbreak is from the intervention of pests such as lizard. Lizard nature which loves to throw feces everywhere is able to contribute to the salmonella outbreaks. Apart from that, direct exposure to touch, skin and lizard droppings are also capable of spreading the salmonella bacteria. Significantly, Prophet Muhammad SAW has warned on threat posed by pest cluster including lizards in his set saying. Thus, this article strives to peel regarding lizard description with the methods to interact with pests through fiqh al-Hadith discussions. This case is important to provide guidance to society regarding harms that able to be incarnated by particular animal and also the most efficient control techniques according to Prophetic tradition without marginalizing animal exclusive rights.